A Systematic Literature Review (SLR): Inclusive Education in the Social-Emotional Development of Elementary School Students - Melyani, Melyani; Amriyah, Chairul; Afriyadi, Muhammad Muchsin (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
In the context of primary education, the implementation of inclusive education represents an important effort to create a fair and equitable education system for all students, particularly in supporting their social-emotional development. Inclusive education emerges as a response to the limitations of the segregated system, which tends to separate students with special needs from their social environment. This study aims to analyze the impact of inclusive education on the social-emotional development of elementary school students using a Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. Data were obtained from reputable databases such as Scopus and SINTA within the 2021–2026 period, through stages of identification, screening, eligibility, and inclusion, resulting in 23 relevant articles for analysis. The analysis was conducted using a bibliometric approach with the assistance of VOSviewer, as well as thematic analysis to identify patterns and research gaps. The results indicate that inclusive education has positive impacts, including increased social interaction, empathy, tolerance, and acceptance of diversity, and also contributes to students’ cognitive development through collaborative learning. However, in certain conditions, inclusive education may present challenges such as anxiety, low self-concept, and difficulties in social adaptation. Its successful implementation is strongly influenced by teacher competence, school readiness, and the support of an inclusive learning environment. Therefore, inclusive education plays a strategic role in shaping students’ social-emotional development, but it requires strengthening in its implementation to achieve optimal outcomes.